The Complexities of 21st Century Brain Exchange - Altbach, Philip (International Higher Education, 2012)
Research by Dongbin Kim, Charles A. S. Bankart, and Laura Isdell ("International doctorates: Trends analysis on their decision to stay in US," Higher Education 62 (August 2011) shows that the large majority of international doctoral recipients from American universities remain in the United States after graduation. Even more surprisingly, the proportion of those choosing to stay in the United States has in- creased over the past three decades, seemingly regardless of growth and academic expansion. There is strong evidence that we live in a worldwide era of global mobility of highly skilled talent in general and of the academic profession in particular, but this mobility flows largely in one direction from developing and emerging economies to the wealthier nations, especially to the English-speaking countries.